2013
DOI: 10.3892/or.2013.2929
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A induces apoptosis in KB human oral cancer cells via a caspase-dependent FasL signaling pathway

Abstract: Licochalcone A (Lico-A) is a natural phenol licorice compound with multiple bioactivities, including anti-inflammatory, anti-microbial, anti-fungal and osteogenesis-inducing properties. In the present study, we investigated the Lico-A-induced apoptotic effects and examined the associated apoptosis pathway in KB human oral cancer cells. Lico-A decreased the number of viable KB oral cancer cells. However, Lico-A did not have an effect on primary normal human oral keratinocytes. In addition, the IC50 value of Lic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…To determine the cellular signaling pathway of Lico-A induced TRAIL expression in FaDu cancer cells, we examined the activation of mitogen-activated protein kinase (MAPK) signaling pathways that have previously been linked to Lico-A-mediated TRAIL expression in the KB human oral cancer cell line (Kim et al, 2014). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the cellular signaling pathway of Lico-A induced TRAIL expression in FaDu cancer cells, we examined the activation of mitogen-activated protein kinase (MAPK) signaling pathways that have previously been linked to Lico-A-mediated TRAIL expression in the KB human oral cancer cell line (Kim et al, 2014). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with 100 and 125 µM Lico-A decreased FaDu cell viability by 50% and 80%, respectively, compared to the non-treated control. Although Zheng et al, reported that the IC 50 value of Lico-A was estimated at approximately 300 µM in the human oral cancer SCC-25 cells (Zeng et al, 2014), the IC 50 value of Lico-A in FaDu cells was estimated at approximately 100 µM, a higher IC 50 value than the 50 µM IC 50 reported for KB human oral cancer cells (Kim et al, 2014). However, IC 50 values of Lico-A was estimated at various dose ranges in other cancer cells.…”
Section: Disscusionmentioning
confidence: 97%
See 1 more Smart Citation
“…LicA decreased the viability of KB human oral cancer cells but had no effect on primary normal human oral keratinocytes [90]. LicA appeared to act by inducing apoptosis that was mediated by the expression of factor associated suicide ligand (FasL) and activated caspases 8 and 3 and PARP [90].…”
Section: Apoptosis and Cell Cycle Effectsmentioning
confidence: 99%
“…Licochalcone A, an anti-inflammatory [1][2][3][4], immunomodulatory [5,6], and antimicrobial [3,5,[7][8][9] polyphenol extracted from Glycyrrhiza inflata [1][2][3]10], triggers apoptosis or inhibits proliferation and migration of tumor cells [11], including those of cervical cancer [12], oral squamous carcinoma [7,9,[13][14][15], esophageal carcinoma [16], gastric cancer [4,17,18], hepatocellular carcinoma [2,19], malignant pleural mesothelioma [20], bladder determined photometrically at 405 nm. The absorption of the supernatant of erythrocytes lysed in distilled water was defined as 100% hemolysis.…”
Section: Introductionmentioning
confidence: 99%